Cardiomyocyte-specific deletion of GSK-3β leads to cardiac dysfunction in a diet induced obesity model. (15th May 2018) - Gupte, Manisha; Tumuluru, Samvruta; Sui, Jennifer Y.; Singh, Anand Prakash; Umbarkar, Prachi; Parikh, Shan S.; Ahmad, Firdos; Zhang, Qinkun; Force, Thomas; Lal, Hind
Abstract: Background and rationale: Obesity, an independent risk factor for the development of myocardial diseases is a growing healthcare problem worldwide. It's well established that GSK-3β is critical to cardiac pathophysiology. However, the role cardiomyocyte (CM) GSK-3β in diet-induced cardiac dysfunction is unknown. Methods: CM-specific GSK-3β knockout (CM-GSK-3β-KO) and littermate controls (WT) mice were fed either a control diet (CD) or high-fat diet (HFD) for 55 weeks. Cardiac function was assessed by transthoracic echocardiography. Results: At baseline, body weights and cardiac function were comparable between the WT and CM-GSK-3β-KOs. However, HFD-fed CM-GSK-3β-KO mice developed severe cardiac dysfunction. Consistently, both heart weight/tibia length and lung weight/tibia length were significantly elevated in the HFD-fed CM-GSK-3β-KO mice. The impaired cardiac function and adverse ventricular remodeling in the CM-GSK-3β-KOs were independent of body weight or the lean/fat mass composition as HFD-fed CM-GSK-3β-KO and controls demonstrated comparable body weight and body masses. At the molecular level, on a CD, CM-GSK-3α compensated for the loss of CM-GSK-3β, as evident by significantly reduced GSK-3αs21 phosphorylation (activation) resulting in a preserved canonical β-catenin ubiquitination pathway and cardiac function. However, this protective compensatory mechanism is lost with HFD, leading to excessive accumulation of β-catenin in HFD-fed CM-GSK-3β-KO hearts, resulting in adverse ventricular remodeling and cardiac dysfunction. Conclusion: In summary, these results suggest that cardiac GSK-3β is crucial to protect against obesity-induced adverse ventricular remodeling and cardiac dysfunction. Highlights: The role of cardiomyocytes (CM) GSK-3β in obesity-associated cardiac dysfunction is unknown. Herein, we show that CM-Specific deletion of GSK-3β leads to severe cardiac dysfunction in a diet-induced obesity model. Mechanistically, on a control diet, CM-GSK-3α compensated for the loss of CM-GSK-3β to preserve the β-catenin ubiquitination and cardiac function. However, the protective mechanism is lost with HFD, leading to excessive β-catenin accumulation and cardiac dysfunction. These data provides a cautionary note for the potential adverse consequences of chronic GSK-3 inhibition in the heart.